Reconditioning of circulatory death hearts by ex-vivo machine perfusion with a novel HTK-N preservation solution - Saemann, Lars; Korkmaz-İçöz, Sevil; Hoorn, Fabio; Veres, Gábor; Kraft, Patricia; Georgevici, Adrian-Iustin; Brune, Maik; Guo, Yuxing; Loganathan, Sivakkanan; Wenzel, Folker; Karck, Matthias; Szabó, Gábor (The journal of heart and lung transplantation, 2021)
Background - Warm ischemia followed by blood reperfusion is associated with reduced myocardial contractility. Circulatory death (CD) hearts are maintained by machine perfusion (MP) with blood. However, the impact of MP with histidine-tryptophane-ketoglutarate (HTK) or novel HTK-N solution on reconditioning of CD-heart contractility is unknown. - Methods - In a porcine model, native hearts were directly harvested (control), or CD was induced before harvesting, followed by left ventricular (LV) contractile assessment. In MP-groups, CD-hearts were maintained for 4 h by MP with blood (CD-B), cold oxygenated HTK (CD-HTK) or HTK-N (CD-HTK-N) before contractile evaluation (all groups n = 8). We performed immunohistochemistry of LV myocardial samples. We profiled myocardial expression of 84 oxidative stress-related genes and correlated the findings with myocardial contractility via a machine learning algorithm. - Results - HTK-N improved end-systolic pressure (ESP=172±10 vs 132±5 mmHg, p = 0.02) and maximal slope of pressure increment (dp/dtmax=2161±214 vs 1240±167 mmHg/s, p = 0.005) compared to CD, whereas CD-B failed to improve contractility. Dp/dtmax (2161±214 vs 1177±156, p = 0.08) and maximal rate of pressure decrement (dp/dtmin=-1501±228 vs -637±79, p = 0.005) were also superior in CD-HTK-N compared to CD-B. In CD-HTK-N, myocardial 4-hydroxynonenal (marker for oxidative stress; p<0.001), nitrotyrosine (marker for nitrosative stress; p = 0.004), poly(adenosine diphosphate-ribose)polymerase (marker for necrosis; p = 0.028) immunoreactivity and cell swelling (p = 0.008) were decreased compared to CD-B. Strong correlation of gene expression with ESP was identified for oxidative stress defense genes in CD-HTK-N. - Conclusion - During harvesting procedure, MP with HTK-N reconditions CD-heart systolic and diastolic function by reducing oxidative and nitrosative stress and preventing cardiomyocytes from cell swelling and necrosis.
Gesehen am 10.02.2022